Mexicans on the Move: Migration and Return in Rural Mexico - Rothstein, Frances A.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This book describes and analyzes migration of individuals from San Cosme Mazatecochco in central Mexico to a new United States community in New Jersey. Based on four decades of anthropological research in Mazatecochco and among migrants in New Jersey Rothstein traces the causes and consequences of migration and who returned home, why, and how return migrants reintegrated back into their homeland.
Keywords: Ethnology; Migration; Ethnology-Latin America